Internalisasi Kegiatan “Jum’at Shodaqoh” dalam Membentuk Sikap Kepedulian Sosial Siswa MA Nahdlatul Ulama’ Kraksaan Probolinggo - Nahdiyatul Husna; Herwati (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
The aim of this research is to analyze the internalization of the value of Islamic religious education through the "Friday Shodaqoh" activity to form the students of MA Nahdlatul Ulama Kraksaan to have social care attitudes and good attitudes towards fellow human beings and apply them in everyday life. This descriptive qualitative research, data collection through direct observation to the field, interviews and documentation. The results of this study are MA Nahdlatul Ulama Kraksaan programs religious extracurricular activities with Friday Shodaqoh activities, the habit of "Friday Shodaqoh" is an activity in the form of infaq every Friday which is sunnah1 and has been carried out for more than 4 years. This infaq activity is not determined in nominal value, after the collected funds are handed over to the treasurer or homeroom teacher, then it is coordinated by the teacher in charge of holding the infaq money. pedicab drivers and others. The formation of social care attitudes in students can be seen from the patterns of thinking, attitudes and behavior that are getting better day by day.